11-10x=-(4+7x)

Simple and best practice solution for 11-10x=-(4+7x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-10x=-(4+7x) equation:


Simplifying
11 + -10x = -1(4 + 7x)
11 + -10x = (4 * -1 + 7x * -1)
11 + -10x = (-4 + -7x)

Solving
11 + -10x = -4 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
11 + -10x + 7x = -4 + -7x + 7x

Combine like terms: -10x + 7x = -3x
11 + -3x = -4 + -7x + 7x

Combine like terms: -7x + 7x = 0
11 + -3x = -4 + 0
11 + -3x = -4

Add '-11' to each side of the equation.
11 + -11 + -3x = -4 + -11

Combine like terms: 11 + -11 = 0
0 + -3x = -4 + -11
-3x = -4 + -11

Combine like terms: -4 + -11 = -15
-3x = -15

Divide each side by '-3'.
x = 5

Simplifying
x = 5

See similar equations:

| 0.5t^3-1.5*t^2*k+6*t*k-6t+50=0 | | (18*18)+(24*24)=x*x | | (6x-5t)(7x+5t)= | | m=4a+(10)2c(5) | | 2(7+2x)=50 | | -7(5-8x)=-483 | | 8g=30 | | 3+7x=9+x | | (9*9)+(12*12)=x*x | | 1+ln(x+8)=2ln(2) | | (25/108)*(1/3) | | 6/x=4/14 | | 2sinx=3 | | f(x)=1-x-2 | | 6p+6(5+p)=90 | | y=5cos(5x) | | 3n(7n-20)=90 | | (2a^5b)^5/40b^4 | | 0.5+4=7 | | 6(4n+1)-4n=106 | | y=2-x+2 | | p/15t-700 | | y=2-x-2 | | -2(-7m+1)=-100 | | 3x-9y=-17 | | a^2-2a-2=0 | | 6.7x-1=5.7x | | 289=-16t^2+vot | | 5x^3-20x^2+x=0 | | -7[-3+-4]= | | 1.25x^2-2x=1 | | log(x)=7.5 |

Equations solver categories